What Makes a Brand Successful? A Case-study of Musette Brand - KULCSÁR, Erika; FILIP, Borostyán Viktória (Studia Universitatis Babeș-Bolyai Negotia, 2024)
The study of gender differences has recently become a growing focus. Nothing is more evidence of this than the fact that in 2023 Claudia Goldin (who studied the position of women in relation to the labour market) was awarded the Nobel Prize in Economics. Furthermore, internationally, there are numerous studies that examine the differences between women and men as leaders and managers. The question arises as to what factors play a significant role from the perspective of women managers in starting and managing a successful business. The present research focuses on the analysis of a Romanian brand - Musette - which is co-founded by a woman (through Cristina Bâtlan) and is represented internationally. Despite the considerable success of the Musette brand, there is a lack of literature in Romania on the study of this brand. Consequently, the objectives of our study are: (1) to identify the conditions that should be the pillars of a start-up business, (2) to identify the factors without which there is no possibility of further development and lasting success, and (3) to examine the brand personality characteristics of Musette. JEL classification: M10, M31 Article History: Received: March 5, 2024; Reviewed: July 10, 2024; Accepted: August 7, 2024; Available online: September 23, 2024